Illustrative action programs - Roggenkamp, Janice; Illinois State Office of the Superintendent of Public Instruction, Springfield ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1966)
This report summarizes some of the counseling practices employed in various demonstration centers. Students were assisted through individual and group counseling. In one center, successful test interpretation interviews resulted from a comparison of students' estimated test results and actual test results. Students learned of occupations through resource speakers and studies of job fields. In one library, information was used to establish "world of work" and "about myself" sections. Counselors also helped to organize extracurricular activities and to solve student problems. Through consultation with counselors, teachers were assisted in becoming more accepting and in solving grouping, placement, and discipline problems. A guidance program in one center developed forms to facilitate teachers' understanding and evaluation of pupils. Interstaff communication was improved in one school when teachers exchanged classes for a day. A successful inservice program was based on a poll of what teachers desired to learn. Other inservice programs helped teachers gather information about pupils and organize parent-teacher conferences. One counselor group helped teachers organize a three-session, parent-teacher conference program which served to help both teacher and parent to understand the child better, acquaint parents with the school's program, bring the parents and teacher together, and improve public relations. This is one of the reports from the zion conference and the elementary school demonstration centers included in "elementary school guidance in Illinois." (ps)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Classroom Guidance Programs; Consultants; Counseling Services; Group Counseling; Guidance Programs; Inservice Teacher Education; Occupational Information; Parent Attitudes; Parent Teacher Conferences; Parent Teacher Cooperation; Reading Programs; Student Evaluation; Test Interpretation; Illinois (Springfield)